Cryptococcus neoformans infective endocarditis of native valves in an immunocompetent host. (2018) - Roy, Moni; Ahmad, Sharjeel; Roy, Ashish Kumar
Abstract: With the emergence of Human immunodeficiency virus (HIV) and the resulting immunocompromised state, Cryptococcus neoformans infections have gained more importance in clinical practice. Cryptococcal infections in immunocompetent hosts continue to be uncommon. We present a rare case of Cryptococcus neoformans infective endocarditis (IE) in a young immunocompetent male. As per our literature review, this is the first reported case of native valve Cryptococcus neoformans endocarditis in an immunocompetent host. All cases till date have been reported in patients with underlying immunocompromised state or prosthetic valve.